Applying Some Indices for Soil Pollution Assessment in Northern Industrial Area from Erbil Governorate - Nashmeel Khudhur; Sidra Qubad Yassin; Ahmed Saman Hassan; Mortatha Nawzad Omar (Al-Qadisiyah Journal of Pure Science, 2021)
Soil pollution by some heavy metals including: Cr, Mn, Fe, Ni, Cu, Zn, As, Mo, Cd and Pb from northern industrial area of Erbil City was assessed. The contamination indices including: geoaccumulation (Igeo), contamination factor (CF), enrichment factor (EF), degree of contamination (Cdeg), pollution load index (PLI) and element contamination index (ECI) were applied to assess soil pollution in Erbil North Industrial area at three sites (for both surface and sub-surface soils). Maximum Fe value 34243.6 ppm was recorded in sub-surface soil (site 2). Maximum values 265.4, 248.8, 98.23 and 397.45 ppm were recorded for Cr, Ni, Cu and Zn at sub-surface soil (site 3). Whereas, maximum values of 22.52, 5.36, 23.9, 6.12 and 65.67 ppm were recorded for As, Mo, Ag, Cd and Pb at surface soil (site 3). Results of analysed heavy metals for soil Cr, Mn, Fe, Ni, Cu, Zn, As, Mo, Ag, Cd and Pb have shown that the studied sites were severely contaminated with Cd, so the maximum detected Cd concentration was 6.12 ppm in surface soil (300 meters away from the industrial area). The soil pollution in the studied area was classified as moderate to strong surface and sub-surface soil contamination. Behavioral toxicity experiment showed slight growth effect on Lepidium sativum L.